2011
DOI: 10.1021/ja2063956
|View full text |Cite
|
Sign up to set email alerts
|

Local Release of Highly Loaded Antibodies from Functionalized Nanoporous Support for Cancer Immunotherapy

Abstract: Recent advances with functionalized nanoporous supports provide an innovative approach for entrapping proteins and for their subsequent controlled release and delivery.1 -7 Functionalized mesoporous silica (FMS) can provide a confined and interactive nanoenvironment that increases protein activity and allow large amounts of protein loading compared to unfunctionalized mesoporous silica (UMS) or normal porous silica.5 -7 First, the proteins can be spontaneously entrapped in FMS with rigid, uniform, open nanopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Driven by the electrostatic attraction between positively charged A‐HDMSN and negatively charged protein molecules, A‐HDMSN demonstrate a significantly higher loading capacity of 391 ± 16 μg mg −1 toward β‐Gal and 658 ± 45 μg mg −1 toward IgG ( Figure a), compared to C‐HDMSN (162 ± 19 μg mg −1 to β‐Gal and 416 ± 53 μg mg −1 to IgG). Those values are the highest among the currently reported results . The TGA analysis data (Figure S7, Supporting Information) show a weight loss of 60% contributed by immobilized IgG in A‐HDMSN, which is consistent with the value determined by adsorption method in Figure a.…”
Section: Resultssupporting
confidence: 87%
“…Driven by the electrostatic attraction between positively charged A‐HDMSN and negatively charged protein molecules, A‐HDMSN demonstrate a significantly higher loading capacity of 391 ± 16 μg mg −1 toward β‐Gal and 658 ± 45 μg mg −1 toward IgG ( Figure a), compared to C‐HDMSN (162 ± 19 μg mg −1 to β‐Gal and 416 ± 53 μg mg −1 to IgG). Those values are the highest among the currently reported results . The TGA analysis data (Figure S7, Supporting Information) show a weight loss of 60% contributed by immobilized IgG in A‐HDMSN, which is consistent with the value determined by adsorption method in Figure a.…”
Section: Resultssupporting
confidence: 87%
“…The IgG loading capacity of MSN-CC is comparable to that of silica foams with a large pore of 30 nm (≈610 mg g −1 ). [ 8 ] Besides high loading capacity, effi cient cellular uptake is another prerequisite factor for protein delivery. To investigate cellular internalization of the particles, MSN-CC were modifi ed with 3-aminopropyltriethoxysilane then conjugated with a red fl orescence molecule, rhodamine B isothicyanate (RITC).…”
Section: Resultsmentioning
confidence: 99%
“…Traditional MSNs usually have small pore sizes, thus their applications are limited for the delivery of small proteins . Foam‐like silica materials with a pore size of 30 nm have been utilized to load large proteins (Immunoglobulin G, IgG); however, their micrometer particle size is not desired for cellular delivery. Bale et al reported the successfully intracellular delivery of antibody into cells by hydrophobically functionalized solid silica nanoparticles; however the loading capacity was relatively low.…”
Section: Introductionmentioning
confidence: 99%
“…over systemic injection of immunomodulatory mAbs has also been demonstrated by others, primarily as an approach to reduce systemic toxicity (20, 45, 46). To further improve its therapeutic window one may obtain a sustained high intratumoral level by entrapping the mAbs in nanoparticles (47) or by using constructs that combine immunomodulatory mAbs with tumor-targeting ones; if the targeting is efficient, the constructs may be administered systemically.…”
Section: Discussionmentioning
confidence: 99%